Investigation of frequency and temperature dependence on dielectric properties of cobalt zinc sulfide compounds prepared by co-precipitation route. (1st February 2023) - Rao, V. Laxminarasimha; Reddy, Y. Vasudeva; Kumar, T. Suresh; Kumar, N. Pavan; Kunta, Bhanu Prasad; Nagabhushanam, M.
Abstract: Co-Precipitation technique used to synthesize Cox Zn1-x S ternary compounds. Samples were studied for their ac conductivity between 30 °C and 300 °C, in the range of 50 Hz to 20 MHz. Analysis revealed that AC conductivity of the samples, correlating with the CBH model. It shows a diminishing trend with rise in frequency, and at higher frequencies the value is more or less constant. The dielectric constant increases with an increase in temperature and cobalt concentration, and it reaches a higher value at lower frequencies. When compared, the values of the samples dielectric loss reveal a trend that is consistent with the value of the dielectric constant. The phenomena that was investigated in this research is thought to be caused by cobalt interstitial defects, which are produced when cobalt ions are introduced into zinc sulfide. Highlights of the work: AC conductivity of Cox Zn1-x S compounds exhibit correlated barrier hopping type of conduction. The grain contribution is more for AC conductivity of Cox Zn1-x S compounds. Both є ′ a n d tan δ < ! − − Q 3 : H i g h l i g h t s s h o u l d o n l y c o n s i s t o f 125 c h a r a c t e r s p e r b u l l e t p o i n t, i n c l u d i n g s p a c e s . T h e h i g h l i g h t s p r o v i d e d a r e t o o l o n g ; p l e a s e e d i t t h e m t o m e e t t h e r e q u i r e m e n t . − − > were low in high frequency regime; this behavior indicated that the compound acquires superior optical quality with lesser defects. This is a crucial parameter in designing of optoelectronic devices.